The graphic works by Anton P. Losenko (1737-1773): foreign infl uence and national identity - Otrishko, Alexandra O. (Actual Problems of Theory and History of Art, 2012)
The article is dedicated to the graphic works of Anton Losenko (1737-1773), who is known as an outstanding painter and graphic artist and is believed to be the founder of drawing school in Russia. The artist was one of the fi rst pensioners of Russian Academy of Arts. The period of his studying in France coincided with the turn from Rococo to Classicism, which undoubtedly influenced Losenko’s work. However, it is incorrect to call Losenko an imitator of the French school. The artist returned to Russia full of new skills and new ideals that later became fundamental for the new Russian drawing school.
Keywords: graphic works of Anton Losenko; art conversion from Rococo to Classicism; Russian Academy of Fine Arts; French school of drawing